"In sickness and in health, in poverty and in wealth?": Economic crises and CSR change management in difficult times. Issue 1 (12th February 2018) - Roman Pais Seles, Bruno Michel; Lopes de Sousa Jabbour, Ana Beatriz; Chiappetta Jabbour, Charbel Jose; Jugend, Daniel
Abstract : Purpose: "Economic crises" and "corporate social responsibility (CSR) initiatives" are two issues that dominate the modern business agenda. Although related, these issues have been analysed separately, and so a significant gap is perpetuated between the two. What are the effects of economic crises on CSR initiatives? Can organisational social initiatives withstand economic crises? The purpose of this paper is to answer these questions. Design/methodology/approach: An integrative literature review was conducted, considering: the economic and geographical context in which the research was conducted; the focus of each piece of research; the adopted research methods; organisational theories of analytical support; the sectors analysed; and the effects of economic crises on CSR initiatives and environmental management. Findings: Some of the findings were as follows: most of the studies analysed reported that CSR helps companies to cope with economic crises by increasing the efficiency of investments and establishing better relations with stakeholders and markets; environmental practices are related to negative environmental performance in periods of economic crises; and CSR relates positively to financial performance in periods of economic crises. Originality/value: This is one of the first integrative literature reviews to investigate what happens to the relationship between businesses and sustainable change management in periods of crises. This paper also offers a future research agenda for the issue, with 12 questions still unanswered by the latest research.